Shaping the campus conversation on student learning and experience activating the results of assessment in action - Brown, Karen E.; Gilchrist, Debra L.; Goek, Sara; Hinchliffe, Lisa Janicke; Malenfant, Kara Josephine; Ollis, Chase; Payne, Allison (Association of College and Research Libraries, a division of the American Library Association, 2018)
Shaping the Campus Conversation on Student Learning and Experience serves anyone seeking to activate the results of the AiA program: academic librarians new to assessment; libraries that have ongoing assessment programs and are looking for new directions or ideas for expanding their efforts; librarians demonstrating to campus administrators the library's impact on student learning and success; campus assessment officers and higher education administrators; and library and information science faculty and scholars